MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN MENGGUNAKAN MEDIA SUKU KATA KELAS II SD NEGERI JATI 2 KECAMATAN ASTAMBUL KABUPATEN BANJAR - Anisah; Rabiatul Adawiyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Indonesian language learning in elementary schools aims to develop students’ oral and written communication skills. This study aimed to analyze students’ early reading ability, student activities, teacher activities, and students’ responses to the use of flannel board media among second-grade students at SD Negeri Jati 2, Banjar Regency, South Kalimantan. The study employed a Classroom Action Research (CAR) design with a descriptive approach. Data were collected through reading tests, observations, questionnaires, and interviews, and analyzed descriptively. The findings revealed that the use of flannel board media significantly improved students’ early reading skills. Teacher performance increased from the “good” category in Cycle I to the “very good” category in Cycle II. Students’ classical learning mastery also improved substantially, rising from 14.28% in the Cycle I pretest to 86% in the Cycle II posttest. Furthermore, students showed a highly positive response to the learning media, with an average response rate of 90.28%. Therefore, flannel board media proved effective in improving early reading skills among second-grade elementary school students.